2017
DOI: 10.1093/neuros/nyx090
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable Grading System for Prediction of Chronic Subdural Hematoma Recurrence Requiring Reoperation After Initial Burr-Hole Surgery

Abstract: BACKGROUNDThere is no widely adopted grading system for the prediction of postoperative recurrence requiring reoperation (RrR) in patients with chronic subdural hematoma (CSDH).OBJECTIVEWe developed a CSDH grading system to predict RrR based on predictive characteristics that can be objectively assessed at the time of first presentation and initial surgery.METHODSProspectively collected data from 107 consecutive surgical patients with CSDH were reviewed. Predictors of RrR were identified via logistic and lasso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
4
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 18 publications
9
81
4
7
Order By: Relevance
“…In 2017, Stanisic et al proposed a grading system for prediction of chronic subdural hematoma recurrence requiring reoperation called the Oslo score, 2 of the 5 maximum possible points being attributed for certain types of the Nakaguchi classification (laminar, separated, isodense and hyperdense). [30] In our study we found a much higher reoperation rate (42,86%) associated to bilateral chronic subdural hematomas, compared to the overall 25%. The fact that bilateral CSDHs associate a much higher recurrence rate compared to unilateral ones has been confirmed by numerous other studies.…”
Section: Relationship Between Csdh's Rrr and Ct Characteristicssupporting
confidence: 40%
“…In 2017, Stanisic et al proposed a grading system for prediction of chronic subdural hematoma recurrence requiring reoperation called the Oslo score, 2 of the 5 maximum possible points being attributed for certain types of the Nakaguchi classification (laminar, separated, isodense and hyperdense). [30] In our study we found a much higher reoperation rate (42,86%) associated to bilateral chronic subdural hematomas, compared to the overall 25%. The fact that bilateral CSDHs associate a much higher recurrence rate compared to unilateral ones has been confirmed by numerous other studies.…”
Section: Relationship Between Csdh's Rrr and Ct Characteristicssupporting
confidence: 40%
“…Although the commonly used techniques are relatively safe and simple (1), cSDH have a mortality rate as high as 42% (5,6) and a recurrence rate up to 76% (1,7,8). Prediction models so far have been inconsistent (9)(10)(11)(12) and are not routinely implemented in clinical practice. In addition, questions regarding postoperative OAC and APD management remain unanswered (1).…”
Section: Introductionmentioning
confidence: 99%
“…The reported rate ranges from 9.2% to 26.5%. 1,2,[10][11][12]15 Moreover, in bcSDHs the retreatment rate reaches almost 30%. 7,13,19 Noted retreatment rates for bcSDHs in the literature depict both surgery for ipsilateral recurrence and surgery for contralateral progression after initial unilateral hematoma evacuation.…”
mentioning
confidence: 96%